DIGESTIVE COMPLICATIONS IN A CHILD WITH DOWN SYNDROME - CASE REPORT - Gabriela Păduraru; Marin Burlea; Smaranda Diaconescu; Valeriu V. Lupu; Claudia Olaru; Nicoleta Gimiga; Gabriela Ciubotariu; Petru Plămădeală; Ovidiu Bărbuţă; Simona Gavrilescu; Ancuța Ignat (Romanian Society of Oral Rehabilitation, 2015)
Down syndrome, also known as trisomy 21, is a genetic disorder caused by the presence of all or part of a third copy of chromosome 21. Megacolon is an abnormal dilation of the colon, often accompanied by a paralysis of the peristaltic movements of the bowel. Congenital megacolon occurs in 1 in 5000 births. The incidence increased with the presence of Down syndrome. Congenital megacolon usually becomes manifest in early childhood. The diagnosis is usually made at birth because of meconium ileus or constipation. Plain X-ray shows a caracteristically narrowed distal segment and a dilated proximal colon. The authors present the case of a four months old child hospitalized at the 5th Pediatric Clinics of "St. Mary" Children's Emergency Hospital who was diagnosed with Down syndrome and congenital megacolon. Removal of the functionally abnormal bowel has relieved the patients' symptoms.